2000
DOI: 10.1046/j.1365-2435.2000.t01-1-00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Position‐dependent reproductive success of flowers in Dactylorhiza maculata (Orchidaceae)

Abstract: Summary1. This study explores the importance of flower position for reproductive success of individual flowers of the deceptive terrestrial orchid, Dactylorhiza maculata (L.) Soó. 2. Upper flowers had smaller lips and produced lighter pollinia than those in other parts of the inflorescence, probably due to architectural effects. 3. Dry weight of seed capsules decreased from bottom to top in the inflorescence in both open-pollinated and hand-pollinated plants. However, removal of flowers from the middle and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…Indeed, when Darwin (1885: p. 41-42) tested the expectation of seasonally changing fruit set in Dactylorhiza maculata (L.) Soo´, albeit using only six plants, he found that the flowers in the lower halves of the spikes did not consistently have fewer capsules than those in the upper halves. Using samples of 19, 14 and 15 plants, Vallius (2000) found that in open-pollinated Finnish populations of D. maculata, capsule set was greatest in the middle part of the spikes in one year, while there was no difference in capsule production among different spike sections in the other two years. More experiments with individual bees of known foraging history are therefore needed to resolve what tips the balance between bees investing in learning to avoid rewardless plant individuals vs. following other behavioral programs, such as periodically (re-)sampling new and old food sources.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, when Darwin (1885: p. 41-42) tested the expectation of seasonally changing fruit set in Dactylorhiza maculata (L.) Soo´, albeit using only six plants, he found that the flowers in the lower halves of the spikes did not consistently have fewer capsules than those in the upper halves. Using samples of 19, 14 and 15 plants, Vallius (2000) found that in open-pollinated Finnish populations of D. maculata, capsule set was greatest in the middle part of the spikes in one year, while there was no difference in capsule production among different spike sections in the other two years. More experiments with individual bees of known foraging history are therefore needed to resolve what tips the balance between bees investing in learning to avoid rewardless plant individuals vs. following other behavioral programs, such as periodically (re-)sampling new and old food sources.…”
Section: Discussionmentioning
confidence: 96%
“…Corolla lip length of the orchid Dactulorhiza declines with flower position but spur length does not [82]. In flowers of Aquilegia canadensis, nectar spur, gynoecium and stamen lengths are invariant with position while the size of the showy sepals declines [83].…”
Section: Architectural Effects On Integration and Modularity?mentioning
confidence: 95%
“…Although fruit size and/or fruit set declines have been shown in several species in earlier studies (reviewed in Diggle 2003), these were attributed either to competition for resources (Medrano et al 2000;Vallius 2000;Kliber and Eckert 2004) or to architectural constraints (Byrne and Mazer 1990;Wolfe and Denton 2001;Guitián et al 2001). Very likely, the relative importance of architectural constraints and resource competition is species-or even trait-speciWc (Ashman 1992;Wolfe 1992;Diggle 1997;Ashman and Hitchens 2000;Kliber and Eckert 2004).…”
Section: Resource Competition Versus Architectural Evectmentioning
confidence: 98%
“…The investment decline in Xowers and fruits has most often been described for linear inXorescences, such as racemes (Byrne and Mazer 1990;Susko and Lovett-Doust 1999;Vallius 2000;Kudo et al 2001;Wolfe and Denton 2001;Hiraga and Sakai 2007;Zeng et al 2008). Although position eVects are also known in plants having other inXorescence architectures, such as umbels (Wyatt 1980) and capitula (Zohary 1950;Burtt 1977), these structures have been studied much less.…”
Section: Introductionmentioning
confidence: 99%